2009
DOI: 10.1002/jnm.720
|View full text |Cite
|
Sign up to set email alerts
|

Advanced models for transient analysis of lossy and dispersive anisotropic planar layers

Abstract: SUMMARYA new model is proposed for the transient analysis of the electromagnetic field propagation through anisotropic lossy and dispersive layers. The propagation equations of the electromagnetic fields are solved as a Sturm-Liouville problem leading to identify its dyadic Green's function in a series rational form. Then, the corresponding poles and residues are obtained and a reduced order macromodel is generated, which can be easily embedded within existing three dimensional solvers. The model is applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Full wave analyses of antenna performance in time domain, 6 in spectral domain, 7 and by approximation method 8 were applied to show that the resonant frequency is decreased by the overlay (when embedded) due to surface wave loss. 9 Similar investigations on microstrip antenna with dielectric overlay 10 and oxide overlay 11 also confirmed that the embedding can reduce antenna gain substantially. The above studies, however, were limited to antenna on isotropic structures.…”
Section: Introductionmentioning
confidence: 57%
“…Full wave analyses of antenna performance in time domain, 6 in spectral domain, 7 and by approximation method 8 were applied to show that the resonant frequency is decreased by the overlay (when embedded) due to surface wave loss. 9 Similar investigations on microstrip antenna with dielectric overlay 10 and oxide overlay 11 also confirmed that the embedding can reduce antenna gain substantially. The above studies, however, were limited to antenna on isotropic structures.…”
Section: Introductionmentioning
confidence: 57%